Strategi Blue Ocean dalam Meningkatkan Daya Saing Lembaga Pendidikan Islam di Era Digital - Himmah, Aliyatul; Siregar, Wanidi (J-MPI (Jurnal Manajemen Pendidikan Islam), 2025)
The era of globalization compels Islamic educational institutions to continuously innovate in order to remain relevant and competitive amidst increasingly complex market dynamics. This study aims to describe the implementation of the Blue Ocean Strategy at Madrasah Aliyah Ihsaniyya Yogyakarta as an effort to strengthen adaptive strategic management oriented toward creating new market spaces. This research employed a qualitative method with a descriptive analytical approach, utilizing observation, in-depth interviews, and documentation techniques. The findings indicate that Madrasah Aliyah Ihsaniyya applies the three main characteristics of the Blue Ocean Strategy focus, divergence, and a compelling motto realized through its Digital Entrepreneurship program integrated with Islamic values. This strategy enables the madrasah to build a competitive advantage without being trapped in conventional competition (Red Ocean). These findings highlight the critical role of value innovation in developing strategic management within Islamic educational institutions to enhance quality, relevance, and competitiveness in the digital era. It is expected that this study can serve as a reference for education managers in designing creative and contextual strategic management frameworks.